ANALISIS VIDEO CLIP TONGTOLANG SAMBASUNDA DALAM PERSPEKTIF SEMIOTIKA ROLAND BARTHES - Anggit Surya Jatnika (Institut Seni Budaya Indonesia Bandung, 2022)
ABSTRACT This study analyzes the audio-visual video clip of Tongtolang Sambasunda. The purpose of this study is to reveal the symbols in the Tongtolang Sambasunda video clip. Video clip is one of the symbolic communication media that functions as a conveyer of information to the public. This study uses Roland Barthes' symbolic approach, namely the